Autozygome sequencing expands the horizon of human knockout research and provides novel insights into human phenotypic variation. - Ahmed B Alsalem; Anason S Halees; Shamsa Anazi; Shomoukh Alshamekh; Fowzan S Alkuraya (PLoS Genetics)
The use of autozygosity as a mapping tool in the search for autosomal recessive disease genes is well established. We hypothesized that autozygosity not only unmasks the recessiveness of disease causing variants, but can also reveal natural knockouts of genes with less obvious phenotypic consequences. To test this hypothesis, we exome sequenced 77 well phenotyped individuals born to first cousin parents in search of genes that are biallelically inactivated. Using a very conservative estimate, we show that each of these individuals carries biallelic inactivation of 22.8 genes on average. For many of the 169 genes that appear to be biallelically inactivated, available data support involvement in modulating metabolism, immunity, perception, external appearance and other phenotypic aspects, and appear therefore to contribute to human phenotypic variation. Other genes with biallelic inactivation may contribute in yet unknown mechanisms or may be on their way to conversion into pseudogenes due to true recent dispensability. We conclude that sequencing the autozygome is an efficient way to map the contribution of genes to human phenotypic variation that goes beyond the classical definition of disease.